Epidemiological profile of glaucoma patients in Brazil: A systematic review (Research, Society and Development, 2025)
Glaucoma is characterized by increased intraocular pressure affecting retinal ganglion cells and is considered the leading cause of irreversible blindness worldwide. This study aims to outline an epidemiological profile of glaucoma patients, providing a detailed analysis of the prevalence and demographic characteristics of this condition in the Brazilian context. This is a systematic literature review, a survey that gathers and evaluates existing studies and findings to provide an updated overview, identifying patterns, trends, and gaps. It was conducted in the electronic databases PubMed, Scielo, Google Scholar, and VHL, from May to July 2024, using keywords related to the topic. It includes original articles published between July 2014 and July 2024, in Portuguese and English, which will be verified through peer review. As a public health problem, the epidemiological profile highlights the importance of strategies to promote eye health, early detection, and preventive interventions. These actions are essential to prevent or worsen conditions, especially for the most vulnerable groups. Therefore, it is concluded that by outlining the epidemiological profile of glaucoma patients, it is possible to determine which individuals are affected by this comorbidity and for what reason or progression, in order to implement health promotion and prevention measures.